Beyond the Classroom: Expert Teachers’ Perspectives on Developing Innovation Competencies through Design Thinking Practices - Md. Aris, Norliyana; Ibrahim, Nor Hasniza; Abdul Halim, Noor Dayana (Jurnal Pendidikan Bitara UPSI, 2024)
Developing student innovation competencies through STEM education is an essential component of the National STEM Action Plan 2017 - 2025, in line with UNESCO’s 2030 agenda to promote quality and innovation in STEM education. This study explores the perspectives of chemistry expert teachers to analyze the need to develop innovation competencies through design thinking practices among high school chemistry students. The study employs a design and developmental research strategy, emphasizing the needs analysis method during the initial phase. The study gathered data through semi-structured interviews and employed thematic analysis to examine the findings. The study’s findings indicate a strong consensus among experts regarding the importance of developing competencies, particularly problem-solving, goal-oriented thinking, thinking system competencies, group work competencies, and networking competencies, through a design thinking approach. Furthermore, the study identifies a need for more application of teaching approaches based on design thinking in chemistry classes despite the acknowledged potential of this approach. The results emphasize the necessity of creating and applying a Design Thinking Chemistry Module to fill this void and equip teachers with the essential resources and expert guidance to incorporate design thinking into their chemistry lessons successfully.